Zmiany w strukturze społecznej w wyniku transformacji ustrojowej w Polsce. Historyczno-polityczne tło przemian społecznych = Changes in social structure as a result of political transformation in Poland: the historical and political background of social alterations - Janicka, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Following the change of legal and political principles, the rules of social structurisation, along with the connotation of some conceptual categories important for defining social structure, were altered as well. Although political transformation was intentional and expected to produce only positive outcomes, the diagnosis and evaluation of its results for society are still, 20 years later, being examined and discussed.
Keywords: transformacja ustrojowa; struktura społeczna